Development of SI-INTAN Pancasila Learning Media Based on Kotawaringin Barat Local Wisdom - Rini, Endang Setyo; Kartini, Nurul Hikmah; Hendri, Hendri (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Aim: This study aimed to develop and evaluate SI-INTAN Pancasila, an interactive learning media integrating the local wisdom of Kotawaringin Barat into Pancasila Education for Phase B elementary school students. Method: The study employed a Research and Development (R&D) approach using the ASSURE model, involving 24 students of SDN 1 Sungai Rangit Jaya. Data were collected through expert validation, teacher and student response questionnaires, observations, and pretest–posttest assessments. Result and Discussions: The feasibility results showed that the media obtained validation scores of 80% from material experts, 100% from language experts, and 83% from media experts, indicating that the product was highly feasible for classroom use. Practicality data revealed positive responses from both teachers and students, who considered the media engaging and easy to use. The effectiveness of the media was demonstrated by an increase in students’ average learning outcomes from 66.67 on the pretest to 80.00 on the posttest. Conclusion: These findings indicate that SI-INTAN Pancasila is a feasible, practical, and effective learning medium for supporting Pancasila Education while promoting local wisdom values among elementary school students.